Healthy Development : The World Bank Strategy for Health, Nutrition, and Population Results - World Bank (Washington, DC, 2012)
This paper updates the 1997 World Bank Health, Nutrition, and Population Strategy to enhance Bank capacity so that it continues to contribute to this virtuous circle in light of the momentous changes of the past decade in the architecture of development assistance for health (DAH) and of persisting HNP challenges worldwide. This 2007 HNP Strategy outlines the Bank vision for improving its own capacity to respond globally and with a country focus to the urgent issues posed by these changes and challenges.